VALUE PROPOSITION DAN PERSONAL BRANDING DAI DIGITAL: STUDI GUS IQDAM DAN GUS KAUSAR DALAM EKONOMI UMAT - Fatkhullah, Imam; Zen, Muhamad; Zen, Fatmawati (LPPM Universitas Islam Ibrahimy Banyuwangi, 2026)
This study is grounded in the phenomenon of the transformation of da’wah into the digital sphere, which requires preachers not only to deliver religious messages but also to build a unique value proposition and strong personal branding to attract audiences and contribute to the community’s economy. The main research question examines how value proposition and personal branding in digital da’wah shape preacher professionalism and support the strengthening of the ummah’s economy. This study positions itself within the integration of da’wah studies, digital communication, and community economics, which remains underexplored comprehensively. The research employs a qualitative method with a case study approach focusing on Gus Iqdam and Gus Kausar through social media content observation and literature review. The data analysis technique not only follows general stages such as data reduction, data display, and conclusion drawing, but is also strengthened by content analysis and comparative analysis approaches. The findings reveal that both preachers possess distinctive value propositions through communicative styles, humanistic approaches, and relevant content strategies, along with consistent personal branding, which lead to increased audience engagement and contribute to the strengthening of the ummah’s economy through the enhancement of work ethics, economic literacy, and a value-based digital ecosystem.